Studi Kasus: Penerapan Terapi Vokal “aiueo” Pada Klien Stroke Non Hemoragic (SNH) Dengan Masalah Keperawatan Gangguan Komunikasi Verbal - Putri, Novita Surya; Salistia Budi, Yulifah; Inka Sari Dewi, Ni Luh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Stroke is the second highest death disease after heart disease and the third cause of disability in the world. Problems that often arise in sufferers stroke is a verbal communication disorder in which a stroke attacks the left side of the brain and regarding the speech center in people with communication disorders can cause own problems and frustrations. Patients who experience verbal communication disorders. Non-pharmacological therapy will be given, namely giving vocal therapy A, I, U, E, O. This study aims to carry out the Application of AIUEO Vocal Therapy to stroke patient with verbal communication disorder in Internal Medicine Room 1st Floor BLAMBANGAN HOSPITAL. Methods: This writing uses a qualitative study with case study method with a nursing process approach which includes assessment, diagnosis, intervention, implementation, evaluation in doing so also use interview techniques, observation, documentation and source triangulation techniques. Participants used by 2 clients who had nonhemorrhagic strokes with problems verbal communication disorder nursing at Blambangan Hospital. Results: This research with a case study approach after being given AIUEO vocal therapy the result was that after being given vocal therapy AIUEO communication patient 1 from being unable to say the letters E and O to being able and client II from the volume of small sounds becomes louder. Conclusion: Application of AIUEO vocal therapy effectively administered to stroke patients with impaired nursing problems verbal communication.